Liu Wu-Chi et al. (eds.), K'uei Hsing: A Repository of Asian Literature in Translation. Bloomington, University of Indiana Press, 1974. xii, 176 pp. - Maeth Ch., Russell (Estudios de Asia y África, 1978)
-